Association Between Pregnant Woman Class and Pregnancy Complication in Tegal District, Central Java - Maryani, Siti; Respati, Supriyadi Hari; Astirin, Okid Parama (Journal of Maternal and Child Health, 2017)
Background: Maternal mortality amounted to 33 cases in Tegal, Central Java, in 2015. The leading cause of maternal mortality rate in Indonesia was obstetric complication, i.e 46.8%. Pregnancy complication may be affected by maternal age, parity, education, and maternal employment status. Various efforts have been implemented by the government to reduce maternal mortality rate, including pregnant woman class. The objective of the pregnant mother class is to increase maternal knowledge in risk factor detection and to increase their willingness to use antenatal care. This study aimed to estimate the association between pregnant woman class and pregnancy complication, while controlling for confounding factors. Subjects and Method: This was an analytical observational with case control design. This study was conducted at Pagerbarang, Pangkah and Dukuhwaru Health Centers, Tegal, Central Java. A total of 90 study subjects, consisting of 30 laboring women with complication and 60 without complication. The dependent variable was pregnancy complication. The independent variables were maternal age, parity, education, employment status, and participation in pregnant woman class. The data were collected by a set of questionnaire. The data on pregnancy complication was obtained from the obstetric record at the health center. The data were analyzed by multiple logistic regresion. Results: Parity ?3 (OR = 3.47; CI 95% = 0.95 to 12.69; p=0.060) and maternal education <senior high school (OR= 8.58; CI 95% = 1.7 to 43.33; p= 0.009) increased the risk of pregnancy complication. Maternal age 20 to 35 years (OR= 0.26; CI 95% = 0.08 to 0.81; p=0.020), employed